Capture and Control of Material Flows and Stocks in Urban Residential Buildings. (January 2019) - Heinrich, Matthias A; Lang, Werner
Abstract: To promote the circular economy and resource efficiency in the construction industry, information on material flows and stocks is needed. The work presented describes a holistic and dynamic model for the determination of material flows and stocks in urban areas triggered by the construction of residential buildings. In addition to the classification of material stocks (raw material cadastre for residential buildings), it is of central interest to identify future waste streams in order to forecast potential secondary raw materials, determine recovery strategies and control mechanisms. Furthermore, the supply of exploitable fractions must be matched with demand to identify the degree of self-sufficiency of selected areas in order to reduce the use of primary resources and necessary transports. The model developed in this work is validated on the basis of the district of Munich / Freiham, one of the largest urban developments in Germany. In this case study it has been shown that under certain conditions a self-sufficient supply of steel (from 2036 onwards) and recycled aggregate for the production of recycled concrete (from 2031 onwards) for residential building construction can be achieved.